Effect of processing temperature on utilization of whole soybeans by young calves - Abdelgadir, I.E.O.; Morrill, J.L.; Stutts, J.A.; Morrill, B.; Johnson, D.E.; Behnke, Keith C. (Kansas Agricultural Experiment Station, 2012)
Two trials were conducted to determine the optimum conditions for processing whole soybeans for young calves. In the first trial, laboratory procedures and a nitrogen balance study were used. This information was used to design the second trial in which raw and processed soybeans were evaluated in an 8-wk growth trial using 96 Holstein day-old calves. Starters contained soybean meal (SBM), SBM with added fat, raw soybeans, or soybeans processed at 280, 340, or 375°F in a California Pellet Mill Jet-Sploder. Calves fed the starters containing soybeans processed at 340 consumed more feed, gained faster, had lower fecal scores (less scours), and less mortality.
Keywords: Dairy; Temperature; Soybeans; Growth rate; Feed consumption